Methodological Realities: Social Science Methods and Business Reorganizations - Teresa A. Sullivan (Washington University Law Quarterly, 1994)
The objective of this Article is to argue that our methods are appropriate for analyzing business bankruptcy as a class of human and organizational behavior.
Keywords: Bankruptcy reorganization; Social science research; United States; Corporate reorganizations; Social sciences